Interleukin-8 Controls Bacterial Transepithelial Translocation at the Cost of Epithelial Destruction in Experimental Shigellosis - Sansonetti, P. J. (American Society for Microbiology, 1999)
In shigellosis, the network of cellular interactions mediated by a balance of pro- and anti-inflammatory cytokines or chemokines is clearly tipped toward acute destructive inflammation of intestinal tissues by the bacterial invader. This work has addressed the role played by interleukin-8 (IL-8) in a rabbit model of intestinal invasion by Shigella flexneri. IL-8, which is largely produced by the epithelial cells themselves, appears to be a major mediator of the recruitment of polymorphonuclear leukocytes (PMNs) to the subepithelial area and transmigration of these cells through the epithelial lining. Neutralization of IL-8 function by monoclonal antibody WS-4 caused a decrease in the amount of PMNs streaming through the lamina propria and the epithelium, thus significantly attenuating the severity of epithelial lesions in areas of bacterial invasion. These findings are in agreement with our previous work (31). In contrast to the PMNs, the bacteria displayed increased transepithelial translocation, as well as overgrowth in the lamina propria and increased passage into the mesenteric blood. By mediating eradication of bacteria at their epithelial entry site, although at the cost of severe epithelial destruction, IL-8 therefore appears to be a key chemokine in the control of bacterial translocation.